BIMTEK: MENJADIKAN MASYARAKAT WASPADA DAN SIAP SEDIA MENCEGAH "JAGO MERAH" MELAHAP RUMAHNYA, KELUARGANYA, TETANGGANYA, SERTA PEMUKIMANNYA - Anton Abdullah; Wildan Nugraha; Rinto Astutik; Sutiyo Sutiyo; Yacob Mandala Putra Panjaitan; Fitri Masito; Yeti Komalasari; Reyvaldo Fajriansyah Setiawan; Muhammad Iqbal Dwi Saputra; Ridho Priyama Putra (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2021)
The purpose of this community service activity is to provide education regarding efforts to prevent and overcome fire hazards at the Palembang Aviation Polytechnic to minimize the impact of losses caused by fires. The method used was technical guidance in the form of providing basic competence in early fire prevention by using 4 hours of classroom theoretical session and 4 hours of practical session in the field. Overall, this activity went well and smoothly, with the average satisfaction score of participants responses was categorized Very Good (A), indicated that the participants had a very positive response to prevent and control on fire hazard.